Enhancing student engagement and learning outcomes through the PENTAS instructional model - Fatimah Azzahra; Muhammad Saleh (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This study is motivated by low student engagement and learning outcomes. The poor learning outcomes are attributed to a lack of enthusiasm and motivation to participate in the learning process. Furthermore, students' comprehension of the material tends to be slow and superficial, primarily due to inadequate understanding of concepts and the continued reliance on traditional lecture-based teaching methods. This study implements the PENTAS learning model, which integrates problem-based learning, example non-example, and the talking stick method. This study analyses teacher activities, student learning activities, and outcomes. This research employs a qualitative approach using Classroom Action Research (CAR). The findings indicate a significant improvement in teacher activity, with scores increasing from 16 in the first session to 32 in the fourth session. Similarly, student engagement improved from 41% in the first session to 100% in the fourth session. Additionally, student learning outcomes achieved 100% mastery in cognitive, affective, and psychomotor aspects. Based on these results, it can be concluded that the PENTAS learning model effectively enhances teacher activity, student engagement, and overall student learning outcomes.